KAJIAN LEAN CONSTRUCTION PADA PROYEK PEMBANGUNAN JARINGAN IRIGASI SIDILANITANO KABUPATEN TAPANULI UTARA - Asri Afrilliany Surbakti; Mei Brilian Harefa (Universitas Quality, 2021)
Contractors in the construction sector have reduced the cause of their profit, namely the large costs incurred for purchasing construction materials. In utilizing material from construction that is not only for reducing costs incurred, it is more in profit in the project being implemented. The effort used to reduce waste is to use Lean construction (lean construction). The purpose of this study was to analyze the amount of waste generated from the implementation stage of the Sidilanitano irrigation network construction project in North Tapanuli Regency. So that the impact on mitigation is carried out in order to maximize the profit value of the contractor. This research method is a descriptive method and analysis is carried out directly at the project site. Data collection was carried out by field observations, interviews. The results showed that the material that caused waste cost was Pek. Reinforcement, Pek. Formwork and Dismantling Formwork and Pek. Cast Concrete K. 225. The level of application of lean construction in the Sidilanitano irrigation project in North Tapanuli Regency is not yet fully effective. However, the rest of the project material has been optimally carried out by the contractor to a minimum. Where the remaining 50 cm of iron material is stored while smaller sizes are sold. The rest of the concrete material is used to cover the stagnant roads around the project.